Impact of metaverse in health care: a study from the care giver’s perspective - Sebastian, Shaliet Rose; Babu, Bichu P. (International Journal Of Community Medicine And Public Health, 2022)
Background: Metaverse means a world in which virtual and reality interact and coevolve, and social, economic, and cultural activities are carried out in it to create value. The application of metaverse in the field of healthcare can help improving access to healthcare services by overcoming the physical barriers between hospitals and patients, thereby enhancing overall patient satisfaction, particularly in small towns and cities. Objective was to assess the perceptions of doctor interns on the impact of metaverse in the health care field. Methods: This cross-sectional study was conducted among medical graduates doing internship in Pathanamthitta district, central Kerala. A semi structured pilot-tested structured questionnaire was shared among the study participants via a chain-referral procedure. The quantitative data collected was analysed using the software statistical package for social sciences. The responses on participants’ perceptions collected were analysed using the inductive approach of thematic analysis and classified into themes and subthemes. Results: Out of the study participants, 37.6% (150) considered metaverse to be the future of internet. Augmented reality and its applications in real life were the factors that excited a vast majority of the study population. Study participants expressed concerned about data privacy, cyber risks and vulnerabilities. Conclusions: The introduction of metaverse is also not without early challenges.